2015
DOI: 10.1186/s12889-015-1643-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of knowledge, preventive counseling and personal health behaviors on physical activity and consumption of fruits or vegetables in community health workers

Abstract: BackgroundThere is evidence that if a health professional is active and has a healthy diet, he/she is more likely to advise patients about the benefits of physical activity and healthy eating The aims of this study were to: (1) describe the personal physical activity, consumption of fruits and vegetables behaviors and nutritional status of community health workers; (2) evaluate the association between knowledge, delivery of preventive counseling and personal behaviors among community health workers.MethodsThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
24

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 36 publications
4
38
0
24
Order By: Relevance
“…The results of this study conducted through the collection of primary data, with approximately all the CHWs operating in the urban area of a medium-sized city in the southern region of the country bring relevant inputs to be considered in the implementation of CHWs' activities and their primary care actions, in Brazilian municipalities with characteristics similar to Pelotas, Rio Grande do Sul. The studied population consisted almost exclusively of women, as well as in research with the same professionals, in which females represented more than 80% of the samples evaluated [33][34][35] , possibly due to the historical aspects of 34 and Ferraz and Aerts 37 , who demonstrated a higher prevalence of CHWs with 9-11 years of schooling. A survey 38 that evaluated CHWs' schooling level found an increased level of schooling in this professional category, which can be noted considering that about 45% of individuals studied have a professional schooling level.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study conducted through the collection of primary data, with approximately all the CHWs operating in the urban area of a medium-sized city in the southern region of the country bring relevant inputs to be considered in the implementation of CHWs' activities and their primary care actions, in Brazilian municipalities with characteristics similar to Pelotas, Rio Grande do Sul. The studied population consisted almost exclusively of women, as well as in research with the same professionals, in which females represented more than 80% of the samples evaluated [33][34][35] , possibly due to the historical aspects of 34 and Ferraz and Aerts 37 , who demonstrated a higher prevalence of CHWs with 9-11 years of schooling. A survey 38 that evaluated CHWs' schooling level found an increased level of schooling in this professional category, which can be noted considering that about 45% of individuals studied have a professional schooling level.…”
Section: Discussionmentioning
confidence: 99%
“…Only 25% of the cities had plan for training health professionals for develop the actions in "Academia da Saúde". Studies conducted with health professionals in Brazil showed that knowledge is important for physical activity and healthy food promotion in primary health care units 26,27 . The food guide for Brazilian population and book about physical activity promotion in primary health care settings can be good instruments for training these professionals 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Гранична вредност на основу које су испитаници сврстани у физички акти-вне била је најмање 5 дана недељно умереног вежбања у трајању од најмање 30 минута или најмање 3 дана недељно тешке физичке акти-вности у трајању од најмање 20 минута. Ис-питаници би такође задовољили препоручен ниво физичке активности уколико би прово-дили најмање 2 дана недељно радећи вежбе за јачање и тонирање њихових мишића 15 . За питања из другог дела упитника, која се тичу ставова и свести међу студентима о значају физичке активности у домену позити-вног утицаја на квалитет физичког и пси-хичког сегмента живота и даљег унапређења здравља, као и питања која се тичу утврђи-вања разлога за евентуално недовољно бав-љење физичком активношћу, израчуната је процентуална заступљеност.…”
Section: обрада податакаunclassified
“…Студија спроведена у Вијетнаму показала је да студенти у просеку проведу 60 минута дневно бавећи се умере-ном и 20 минута дневно тешком физичком активношћу 18 , што су високе вредности за ову популацију. Разлика у стварном физичком понашању студентске популације може да бу-де повезана са временом када је упитник подељен испитаницима (за време редовног периода предавања или током испитног ро-ка) 15 . Студија која је урађена у Великој Брита-нији у току школске 2007/2008 године даје процену физичке активности студената са седам универзитета.…”
unclassified